Critical Literacy Narratives in Digital Comics: A Semiotic Analysis of Social Critique on Indonesian Webtoons - Muhammadiah, Masud; Amir, Syafiq; Tumusiime, Joseph (Journal of Humanities Research Sustainability, 2024)
Background. Indonesian webtoons have become a dynamic cultural medium, blending visual artistry with episodic storytelling to address pressing social issues. The growing popularity of these digital comics among young audiences creates opportunities for fostering critical literacy, yet systematic analyses of their semiotic strategies remain scarce. This study examines how social critiques are embedded in Indonesian webtoons and how these narratives encourage audiences to engage critically with socio-political realities. Purpose. The research aimed to identify thematic patterns, semiotic modes, and multimodal strategies that contribute to constructing social critique within webtoon narratives. Method. A qualitative design was employed using multimodal semiotic analysis, integrating Kress and van Leeuwen’s framework with Luke and Freebody’s Four Resources Model. Ten Indonesian webtoons were purposively selected based on thematic relevance and popularity, resulting in the analysis of 450 episodes and 3,125 coded instances of semiotic elements. Results. Findings revealed that visual strategies accounted for 58.7% of semiotic instances, with class disparity, gender inequality, and political corruption as dominant themes. Symbolic imagery, color contrasts, and visual metaphors were central to delivering critique, often complemented by textual elements for nuance. Multimodal strategies proved particularly effective in addressing gender issues. Case study evidence from Urban Fractures illustrated how narrative pacing and recurring symbols fostered both individual reflection and participatory audience dialogue. Conclusion. The study concludes that Indonesian webtoons strategically employ visual semiotics to navigate socio-political constraints while promoting critical engagement. The novelty lies in combining multimodal semiotic analysis with critical literacy theory to explore popular digital media as a vehicle for socio-political discourse.